Rorty, Bauman, contingency, and solidarity - Kwiek, Marek (Wydawnictwo Naukowe IF UAM, 1996)
The philosophical excursus presented here differs from all the others. While in the majority of them we presented Rorty’s polemics and discussions with other philosophers - according to the view that Rorty’s philosophy is being coined to a large extent in confrontations with them rather than it is written in isolation, while in one of them we present in an expanded version the picture of what Rorty criticizes (namely we include the Lyotardian concept of the "différend" in the context of the Rortyan inacceptance of it), here we are trying once again to reverse perspectives. We want to show Zygmunt Bauman’s account of the intellectual and the philosopher in the context of Rorty’s account of the role and tasks of the philosopher today presented throughout the book. The point of connection between the two thinkers will be mild criticism of Rorty presented in numerous places by Bauman. Rorty, as far as I know, never responded to it therefore so far the exchange between them is one-sided. But the way of seeing culture,philosophy, modernity and postmodernity as well as intellectuals is so convergent in the two thinkers that I think it is useful to present Bauman’s account of them. This, I hope, will throw additional, although not direct, light to European connections of neopragmatism, and although Rorty does not participate in discussions with Bauman, the closeness of their standpoints produces extremely interesting tensions between them.
Keywords: Richard Rorty; Zygmunt Bauman; American pragmatism; new pragmatism; neopragmatism; intellectuals; American intellectuals; French intellectuals; Bauman's sociology; legislators and interpreters; modernity; postmodernity; the role of the intellectual; social engagement; political engagement; Emil Zola